Becoming a mother during the COVID‐19 pandemic: The lived experience as told by birthing mothers: A qualitative study. (8th November 2022) - Bolgeo, Tatiana; Gambalunga, Francesca; Di Matteo, Roberta; Gatti, Denise; Roberti, Erica; Dealberti, Davide; Fadda, Barbara; Grassi, Elena; Gambarini, Lorella; Iacorossi, Laura; Maconi, Antonio
Abstract: Aims and objectives: The aim of this study is to explore the lived experience of women who gave birth during the COVID‐19 pandemic. Background: Experiencing pregnancy during the Covid‐19 pandemic exacerbates the risk of the onset of psychological problems. Design: This is a descriptive, single‐centre, qualitative study. Methods: The enrolment for data collection included childbearing mothers aged 18 years and over between November 2021 and April 2022. The researchers invited them to write about their personal experiences during the isolation period of the first pandemic wave. The descriptive phenomenological analysis of the data was carried out using the method described by Mortari. Results: A total of 50 mothers were recruited, of whom 28 were primiparous (56.0%) and 22 multiparous (44.0%). From the analysis of the interviews, five main themes emerged that enclose the experience of both primiparous and multiparous mothers: 'The negative feeling: between loneliness, sadness and fear'; 'The comfort of being cared for: between humanity and competence'; 'Family proximity: between comfort and stress'; 'Symbiotic intimacy: bonding; Managing physical pain and consciousness of being resilient women'. Conclusions: The study showed that the discomfort associated with the absence of family support in the phase of labour and childbirth was compensated by the professionalism of the health staff and allowed new mothers to experience moments of great intimacy with the child. Implications for nursing management: Such data could help create recommendations based on the assisted person's experiences to ensure that care is increasingly attentive and tailored to the needs of mothers and, thus, of children.